2016
DOI: 10.1016/j.adro.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative conditioning with total body irradiation for AML: Balancing survival and pulmonary toxicity

Abstract: PurposeThe purpose of this study was to compare leukemia-free survival (LFS) and other clinical outcomes in patients with acute myelogenous leukemia who underwent a myeloablative allogeneic stem cell transplant with and without total body irradiation (TBI).Methods and materialsAdult patients with acute myelogenous leukemia undergoing myeloablative allogeneic stem cell transplant at Duke University Medical Center between 1995 and 2012 were included. The primary endpoint was LFS. Secondary outcomes included over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…1,21 Especially for AML, TBI-based conditioning has traditionally been associated with survival benefits, including lower rates of leukemia relapse, lower TRM, and higher disease-free survival, with comparable adverse events compared to chemotherapy-only conditioning. 6,22,23 This was challenged with the introduction of IV Bu, and in recent analyses of 1230 AML patients, the nonrelapse mortality was significantly less frequent and survival rates were higher in patients receiving IV Bu compared to the TBI group. 24 Another large retrospective multicenter study performed by the European Group for Blood and Marrow Transplantation (EBMT) in 2013 demonstrated that although a TBI-based regimens resulted in a significantly lower incidence of relapse and comparable survival outcomes compared to IV BuCy, it led to higher rates of GVHD in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,21 Especially for AML, TBI-based conditioning has traditionally been associated with survival benefits, including lower rates of leukemia relapse, lower TRM, and higher disease-free survival, with comparable adverse events compared to chemotherapy-only conditioning. 6,22,23 This was challenged with the introduction of IV Bu, and in recent analyses of 1230 AML patients, the nonrelapse mortality was significantly less frequent and survival rates were higher in patients receiving IV Bu compared to the TBI group. 24 Another large retrospective multicenter study performed by the European Group for Blood and Marrow Transplantation (EBMT) in 2013 demonstrated that although a TBI-based regimens resulted in a significantly lower incidence of relapse and comparable survival outcomes compared to IV BuCy, it led to higher rates of GVHD in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…TBI provides therapy to sanctuary sites not easily reached by chemotherapy drugs and provides another mechanism of tumor cell kill against chemotherapy-resistant cell clones. The other is immunosuppression to decrease the risk of graft versus host disease (GVHD) and to enable sustained engraftment [3,4]. However, treatment-related morbidity and mortality can increase, negating any potential advantage for survival [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Both traditional TBI approaches (opposed lateral and AP/PA) use extended source to skin dis-tances (SSDs), custom compensators, blocks, and beam spoilers to ensure adequate skin dose [1]. However, traditional linear accelerator-based delivery has several limitations, including dose-limiting toxicity [2,3]. For men, attempts to use a "clamshell" testicular shield may increase dose due to increased electron scatter [4].…”
Section: Technical Note Introductionmentioning
confidence: 99%